Forced Degradation Studies and Development and Validation of HPLC-UV Method for the Analysis of Velpatasvir Copovidone Solid Dispersion - Bakht Zaman; Waseem Hassan; Adnan Khan; Ayesha Mushtaq; Nisar Ali; Muhammad Bilal; Dina A. Ahmed (Antibiotics, 2022)
Analytical methods for the drug substance and degradation products (DPs) are validated by performing forced degradation studies. Forced degradation studies of Velpatasvir (VEL) drug substance and Velpatasvir copovidone solid dispersion (VEL-CSD) were performed under the stressed alkaline, acidic, oxidative and thermal conditions according to ICH guidelines ICH Q1A (R2). VEL is labile to degrade in stressed alkaline, acidic, and oxidative conditions. It is also photolabile and degraded during photostability studies as described by ICH Q1B, and showed no degradation on exposure to extreme temperature when protected from light. A sensitive stability indicating HPLC-UV method was developed and validated for the separation of VEL and eight DPs. The DPs of VEL are separated using gradient elution of mobile phase containing 0.05% Trifluoroacetic acid (TFA) and methanol over symmetry analytical column C18 (250 mm × 4.6 mm, 5 µm) with a flow rate of 0.8 mL min−1. Simultaneous detection of all DPs and VEL was performed on UV detector at 305 nm. The performance parameters like precision, specificity and linearity of the method were validated using reference standards as prescribed by ICHQ2 (R1). Limits of quantification and limits of detection were determined from calibration curve using the expression 10δ/slope and 3δ/slope respectively. The proposed method is stability-indicating and effectively applied to the analysis of process impurities and DPs in VEL drug substance and VEL-CSD.